OFFER OF PRIVATE BANKING OF KEY BANKS IN POLAND - STATE AND PERSPECTIVES - Sławomir Juszczyk; Karol Gancewski (Polityki Europejskie, Finanse i Marketing)
The aim of the research was to identify and assess the changes of private banking in Poland. The research determined among others that the financial products with the lowest risk are currently the most popular among private banking clients of the surveyed banks. It was also determined that the most popular service in the next 2 years will probably be investment advice. Non-banking services such as legal and tax consultancy, educational consulting or concierge services will be an addition to the private banking in Poland.